Promosi Kesehatan Perilaku Hygiene Pada Siswa SD Di Wilayah Rawan Banjir Jakarta Timur - Fayasari, Adhila; Srimiati, Mia; Istianah, Isti (Universitas Binawan, 2024)
The Ciliwung riverbank area is a water catchment area and is prone to flooding every year, which poses a risk of various kinds of infectious diseases and other health problems. This needs to be prevented by socializing about PHBS (Clean and Healthy Living Behavior) to school children. The aim of this community service activity is to provide education regarding PHBS and the practice of hand washing movements to school-aged children in the Ciliwung riverbank area. This activity was carried out at 7 elementary schools in the East Jakarta and South Jakarta areas in April – May 2018. The results of this activity were an increase in knowledge regarding PHBS for most school groups (score more than 60%). Regular socialization of sanitary behavior is necessary, and the school setting needs to have a sufficient infrastructure for sanitation.